Does a J-curve exist for Korea and Taiwan? - Hsing, Han Min; Savvides, Andreas (My University, 1996)
This article examines whether the trade balance of two dynamic export-oriented economies, Korea and Taiwan, exhibits a J-curve effect. The article studies both their bilateral and aggregate trade balance during the flexible exchange-rate era. When the exchange-rate coefficients are unconstrained, we demonstrate that no J-curve effect exists either for bilateral or aggregate trade balances. Several robustness checks confirm the validity of our findings. When a polynomial-distributed lag structure is imposed on exchange-rate coefficients, a J-curve is evident in some cases. The article discusses possible explanations for the general lack of evidence in favor of a J-curve, including the response of a small country's trade balance to exchange-rate changes.
Keywords: J-curve; Korea; Taiwan; Trade balance